MANAJEMEN KURIKULUM MERDEKA PADA MATA PELAJARAN PPKN DI SMA NEGERI 6 KOTA TERNATE - Kamisi, Mohtar; Wicaksono, Muhammad Arif (Jurnal GeoCivic, 2024)
The independent curriculum is a way to answer the challenges of education that occur due to the post-pandemic education crisis. The curriculum of the learning process is the lack of discipline of teachers in carrying out the learning process in the classroom. For example, often late to class and not preparing teaching materials such as lesson plans and syllabuses during the learning process. This is related to the lack of understanding of teachers about the process of making teaching materials such as lesson plans and syllabuses. This research method uses a descriptive research type through a qualitative approach. Qualitative research is a descriptive research by analyzing through an inductive approach. This study emphasizes the theoretical basis which functions to be the focus of research when in the field. The place of this research will be carried out at SMA Negeri 6 Kota Ternate. The time of implementation of this research was carried out for six months from March to August 2024. The subjects of this research were the Principal, Vice Principal for Curriculum, Vice Principal for Student Affairs, and Teachers. Data collection techniques are observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation, and conclusions. The results of this study indicate that the independent curriculum implemented in SMA Negeri 6 Kota Ternate is still relatively new for teachers and students, related to the implementation of the independent curriculum, many students and teachers are still confused about the implementation of the independent curriculum. One of them is in the PPKn subject. Therefore, teachers must know more about the implementation of the independent curriculum in the learning process at school. Teachers must also understand that the assessment, teaching modules and other components in the independent curriculum with the 2013 curriculum are very different. The independent curriculum is a form of improvement of the 2013 curriculum, of course, there are many responses from several parties, teachers, students, and parents. From several related parties, there are some who support and there are also many who complain about the changes in the independent curriculum that have been implemented.